A phosphate group-modified porous titanium dioxide-silver composite material and its preparation method and application

By modifying the pore-rich titanium dioxide-silver composite material by phosphate groups, the problem of low efficiency of existing TiO2 photocatalysts in the CO2 reduction process is solved, the effect of significantly improving the photocatalytic activity is achieved, and the adsorption and activation ability of CO2 molecules is enhanced.

CN118925757BActive Publication Date: 2025-03-28WUHAN TEXTILE UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410983980.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-03-28
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing TiO2 photocatalysts are inefficient in CO2 reduction, mainly due to their wide band gap, limited utilization of visible light, and fast photogenerated charge recombination rate, which limits their application in photocatalytic reduction of carbon dioxide.

Method used

The pore-rich titanium dioxide-silver composite material modified with phosphate groups was synthesized by solvothermal method, and silver ions were reduced by ammonium hypophosphate and phosphate was introduced to recombinate it with titanium dioxide to enhance photocatalytic activity.

Benefits of technology

It significantly enhances the photocatalytic activity, improves the adsorption and activation ability of CO2 molecules, and improves the transmission and utilization of electron-hole pairs. Compared with monomer materials, it can significantly improve the efficiency of photocatalytic CO2 reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118925757B_ABST
    Figure CN118925757B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of functional materials and photocatalytic material preparation, and specifically to a phosphate group-modified porous titanium dioxide-silver composite material and a preparation method and application thereof. The preparation method comprises the following steps: S1, ultrasonically dispersing modified nano titanium dioxide into deionized water, adding 1 mol / L silver nitrate solution to obtain a mixed solution; S2, adding 1 mol / L sodium hydroxide solution and ammonium hypophosphite to the mixed solution obtained in step S1, putting it into a reactor and heating it for 6-24 hours to obtain a reaction solution; S3, cooling the reaction solution obtained in step S2 to room temperature and washing it with distilled water, and vacuum drying the product at 50-80°C for 10-16 hours to obtain a phosphate group-modified titanium dioxide-silver composite material. The present invention prepares PO4 in one step by a solvothermal method. 3‑ ‑TiO2‑Ag composite material has a simple synthesis process, a stable composite material, Ag is evenly distributed on the TiO2 surface, and has a good catalytic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials and photocatalytic material preparation, and in particular to a porous titanium dioxide-silver composite material modified with a phosphate group, and a preparation method and application thereof. Background Art

[0002] With the rapid development of human society, the exploitation and utilization of traditional fossil fuels has expanded dramatically. 2 The emission of greenhouse gases such as CO2 has also increased dramatically, leading to accelerated climate change. The effective development and utilization of solar energy is one of the important ways to meet these challenges. 2 Reduction technology can convert solar energy into chemical energy that can be easily stored and transported, which is expected to reduce dependence on fossil fuels and help reduce CO 2 net emissions to meet society’s requirements for sustainable development. 2 The C=O bond has a high bond energy (>700 kJ / mol), requiring relatively high energy to undergo CO 2 to hydrocarbon fuels, which also leads to photocatalytic CO 2 Semiconductors with suitable band gaps and high photocatalytic activity are more suitable for photocatalytic CO reduction. 2 Reduction. TiO 2 Due to its stability, non-toxicity, strong redox ability and low price, it has become the most popular CO 2 However, pure TiO 2 CO 2 The conversion efficiency of 2-Hydrogen 2-Pyrrolidone is very low because of its wide band gap, limited utilization of visible light, and fast rate of recombination of photogenerated charges. Its application in photocatalytic reduction of carbon dioxide is greatly limited.

[0003] In recent years, many strategies have been proposed to improve TiO 2 The photocatalytic performance of single TiO 2Among them, metal co-catalyst modification is considered to be an effective method to improve charge separation. Since the Fermi level of n-type semiconductors is higher than that of metals, when n-type semiconductors and metals are in close contact, the energy band bends, and the photogenerated electrons will transfer from the semiconductor to the metal until the Fermi levels of the two are balanced, and the Schottky barrier can inhibit the backflow of electrons, which can further enhance the charge separation efficiency. Among various metal co-catalysts, silver is a relatively excellent co-catalyst. It can not only improve the charge separation ability, but also greatly improve the light absorption of semiconductor materials. And due to the local surface plasmon resonance effect of silver, it can also generate more electrons for photocatalytic CO 2 Reduction reaction.

[0004] In addition to the charge separation efficiency, CO 2 Adsorption and activation of molecules and reactive intermediates for photocatalytic CO 2 In practical studies, some Lewis bases are often used as surface adsorption sites to promote CO 2 Adsorption and activation of molecules such as WO 4 2- , -NH 2 , P.O. 4 3- Related studies have shown that phosphate groups can act as Lewis bases to promote CO 2 In addition to the adsorption of molecules, it also has some special functions, such as enhancing the charge transfer rate and surface redox rate. However, so far, there has been no research on the use of metal co-catalysts with PO 4 3- Co-modification of semiconductor photocatalysts for photocatalytic CO 2 Restore related technologies. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a porous titanium dioxide-silver composite material modified with phosphate groups and a preparation method and application thereof, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a porous titanium dioxide-silver composite material modified with a phosphate group comprises the following steps:

[0008] S1. Ultrasonic dispersion of modified nano-titanium dioxide into deionized water, adding 1 mol / L silver nitrate solution, stirring evenly to obtain a mixed solution;

[0009] S2, adding 1 mol / L sodium hydroxide solution and ammonium hypophosphite to the mixed solution obtained in step S1, stirring for 0.4-0.8 h, putting it into a reactor and heating it at 40-140° C. for 6-24 h to obtain a reaction solution;

[0010] S3, cooling the reaction solution obtained in step S2 to room temperature, washing with distilled water until the supernatant is neutral, washing with anhydrous ethanol for the last time, and vacuum drying the product at 50-80° C. for 10-16 h to obtain a titanium dioxide-silver composite material modified with phosphate groups.

[0011] Furthermore, the modified nano titanium dioxide in step S1 is prepared by the following method:

[0012] S101, ultrasonically dispersing nano-titanium dioxide into a mixed solution of deionized water, ethanol and ethyl propionate, and then adding sodium hydroxide to adjust the pH of the solution to 8-11;

[0013] S102, adding carboxymethyl chitosan, tetraethylene glycol monooctyl ether and sodium styrene sulfonate to the mixed solution of deionized water, ethanol and ethyl propionate in step S101, and then putting the mixture into a reactor to react at 80-160° C. for 4-10 hours;

[0014] S103, filtering the reaction liquid in the reaction kettle after the reaction in step S102, washing with ethanol, and vacuum drying at 150-250° C. to obtain modified nano titanium dioxide.

[0015] Furthermore, in step S101, the mass ratio of ethyl propionate, ethanol and deionized water is 1:3:10, and the mass ratio of nano-titanium dioxide to the mixed solution of deionized water, ethanol and ethyl propionate is 1:(10-30).

[0016] Furthermore, in step S102, the mass ratio of the mixed solution of tetraethylene glycol monooctyl ether, sodium styrene sulfonate and carboxymethyl chitosan to deionized water, ethanol and ethyl propionate is 1:(1-3):(5-10):(80-120).

[0017] Furthermore, in step S1, the mass ratio of the modified nano-titanium dioxide to deionized water is 1:(10-14), and the mass ratio of the silver nitrate solution to deionized water is 1:(26-32).

[0018] Furthermore, the mass ratio of the sodium hydroxide solution in step S2 to the deionized water in step S1 is 1:(15-20), and the mass ratio of the ammonium hypophosphite in step S2 to the deionized water in step S1 is 1:(14-18).

[0019] A phosphoric acid group-modified titanium dioxide-silver composite material is prepared by adopting the preparation method of the phosphoric acid group-modified porous titanium dioxide-silver composite material.

[0020] The invention discloses an application of a titanium dioxide-silver composite material modified with a phosphate group in the field of photocatalytic carbon dioxide reduction to prepare hydrocarbon fuels.

[0021] Furthermore, the application of the titanium dioxide-silver composite material modified with phosphate groups in the field of preparing hydrocarbon fuels by photocatalytic carbon dioxide reduction adopts the following method:

[0022] The titanium dioxide-silver composite material modified with phosphate groups is uniformly mixed with deionized water, and catalytically converts carbon dioxide under light.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention successfully synthesized a titanium dioxide-silver composite material modified with a phosphate group by a solvothermal method. The chemical formula of the composite material is PO 4 3- -TiO 2 -Ag, silver ions are reduced by ammonium hypophosphite to generate silver, phosphate is successfully introduced, and phosphate and silver are compounded with titanium dioxide;

[0025] 2. In the composite material obtained by the present invention, due to TiO 2 The large contact area between Ag and Ag and the abundant surface alkaline sites are conducive to the effective transmission and utilization of electron-hole pairs and the adsorption of CO2 molecules, which can significantly enhance the photocatalytic activity compared with monomer materials.

[0026] 3. The composite material is synthesized in one step, has a simple preparation process, low cost, and convenient operation. The modified nano titanium dioxide is evenly dispersed, and the introduced ammonium radicals generate gas during the hot solvent method, which jointly promotes the uniform attachment of silver ions on the surface of titanium dioxide. The composite material has high stability, meets actual production needs, and has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The process flow chart of preparing the titanium dioxide-silver composite material modified with phosphoric acid groups of the present invention;

[0028] Figure 2 The process flow chart of preparing modified nano titanium dioxide in the present invention;

[0029] Figure 3 This is a scanning electron microscope image (SEM) of the modified nano titanium dioxide in Example 1 of the present invention;

[0030] Figure 4This is a scanning electron microscope image (SEM) of the titanium dioxide-silver composite material modified with phosphate groups in Example 1 of the present invention;

[0031] Figure 5 This is a transmission electron microscopy (TEM) image of the titanium dioxide-silver composite material modified with phosphate groups in Example 1 of the present invention;

[0032] Figure 6 The photocatalytic CO of the titanium dioxide-silver composite material modified with phosphoric acid groups, the nano titanium dioxide and the titanium dioxide modified with phosphoric acid groups in Example 1 of the present invention is 2 Restore activity diagram. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] See also Figure 1-6 , the present invention provides a technical solution:

[0035] Example 1

[0036] A method for preparing a porous titanium dioxide-silver composite material modified with a phosphate group comprises the following steps:

[0037] S1. Disperse 0.3 g of modified nano-titanium dioxide into 70 ml of deionized water by ultrasonic wave at a frequency of 20 kHz, add 0.12 ml of 1 mol / L silver nitrate solution, stir evenly, and obtain a mixed solution;

[0038] S2, adding 4 ml of 1 mol / L sodium hydroxide solution and 0.22 g of ammonium hypophosphite to the mixed solution obtained in step S1, stirring for 0.5 h, and then placing the mixture in a reactor and heating at 80° C. for 15 h to obtain a reaction solution;

[0039] S3, cooling the reaction solution obtained in step S2 to room temperature and washing with distilled water until the supernatant is neutral, washing with anhydrous ethanol for the last time, and vacuum drying the product at 60° C. for 12 h to obtain a titanium dioxide-silver composite material modified with phosphate groups.

[0040] The modified nano titanium dioxide is prepared by the following method:

[0041] S101, ultrasonically dispersing 1.0 g of nano-titanium dioxide into 20 g of a mixed solution containing deionized water, ethanol and ethyl propionate, wherein the masses of deionized water, ethanol and ethyl propionate are 14.3 g, 4.3 g and 1.4 g, respectively, and the frequency of the ultrasonic wave is 18 kHz, and then sodium hydroxide is added to adjust the pH of the solution to 9;

[0042] S102, adding 1.63 g of carboxymethyl chitosan, 0.2 g of tetraethylene glycol monooctyl ether and 0.37 g of sodium styrene sulfonate to the mixed solution of deionized water, ethanol and ethyl propionate in step S101, mixing and placing in a reactor to react at 120° C. for 6 h;

[0043] S103, filtering the reaction liquid in the reaction kettle after the reaction in step S102, washing with ethanol, and vacuum drying at 210° C. to obtain modified nano titanium dioxide.

[0044] Example 2

[0045] A method for preparing a porous titanium dioxide-silver composite material modified with a phosphate group comprises the following steps:

[0046] S1. Disperse 0.6 g of modified nano-titanium dioxide into 60 ml of deionized water by ultrasonic wave at a frequency of 18 kHz, add 0.23 ml of 1 mol / L silver nitrate solution, stir evenly, and obtain a mixed solution;

[0047] S2, adding 4 ml of 1 mol / L sodium hydroxide solution and 0.43 g of ammonium hypophosphite to the mixed solution obtained in step S1, stirring for 0.4 h, and then placing the mixture in a reactor and heating at 40° C. for 24 h to obtain a reaction solution;

[0048] S3, cooling the reaction solution obtained in step S2 to room temperature and washing with distilled water until the supernatant is neutral, washing with anhydrous ethanol for the last time, and vacuum drying the product at 50° C. for 16 h to obtain a titanium dioxide-silver composite material modified with phosphate groups.

[0049] The modified nano titanium dioxide is prepared by the following method:

[0050] S101, ultrasonically dispersing 1.0 g of nano-titanium dioxide into 10 g of a mixed solution containing deionized water, ethanol and ethyl propionate, wherein the masses of deionized water, ethanol and ethyl propionate are 7.12 g, 2.13 g and 0.71 g, respectively, and the frequency of the ultrasonic wave is 15 kHz, and then sodium hydroxide is added to adjust the pH of the solution to 8;

[0051] S102, adding 0.62 g of carboxymethyl chitosan, 0.13 g of tetraethylene glycol monooctyl ether and 0.13 g of sodium styrene sulfonate to the mixed solution of deionized water, ethanol and ethyl propionate in step S101, mixing and placing in a reactor to react at 80° C. for 10 h;

[0052] S103, filtering the reaction liquid in the reaction kettle after the reaction in step S102, washing with ethanol, and vacuum drying at 150° C. to obtain modified nano titanium dioxide.

[0053] Example 3

[0054] A method for preparing a porous titanium dioxide-silver composite material modified with a phosphate group comprises the following steps:

[0055] S1. Disperse 0.5 g of modified nano-titanium dioxide into 84 ml of deionized water by ultrasonic wave at a frequency of 24 kHz, add 0.22 ml of 1 mol / L silver nitrate solution, stir evenly, and obtain a mixed solution;

[0056] S2, adding 3 ml of 1 mol / L sodium hydroxide solution and 0.84 g of ammonium hypophosphite to the mixed solution obtained in step S1, stirring for 0.8 h, and then placing the mixture in a reactor and heating at 140° C. for 6 h to obtain a reaction solution;

[0057] S3, cooling the reaction solution obtained in step S2 to room temperature and washing with distilled water until the supernatant is neutral, washing with anhydrous ethanol for the last time, and vacuum drying the product at 80° C. for 10 h to obtain a titanium dioxide-silver composite material modified with phosphate groups.

[0058] The modified nano titanium dioxide is prepared by the following method:

[0059] S101, ultrasonically dispersing 1 g of nano-titanium dioxide into 30 ml of a mixed solution containing deionized water, ethanol and ethyl propionate, wherein the masses of deionized water, ethanol and ethyl propionate are 21.3 g, 6.37 g and 2.12 g, respectively, and the frequency of the ultrasonic wave is 21 kHz, and then sodium hydroxide is added to adjust the pH of the solution to 11;

[0060] S102, adding 0.62 g of carboxymethyl chitosan, 0.12 g of tetraethylene glycol monooctyl ether and 0.12 g of sodium styrene sulfonate to the mixed solution of deionized water, ethanol and ethyl propionate in step S101, mixing and placing in a reactor to react at 160° C. for 4 h;

[0061] S103, filtering the reaction liquid in the reaction kettle after the reaction in step S102, washing with ethanol, and vacuum drying at 250° C. to obtain modified nano titanium dioxide.

[0062] Example 4

[0063] A method for preparing a porous titanium dioxide-silver composite material modified with a phosphate group comprises the following steps:

[0064] S1. Disperse 0.3 g of modified nano-titanium dioxide into 76 ml of deionized water by ultrasonic wave at a frequency of 21 kHz, add 0.16 ml of 1 mol / L silver nitrate solution, stir evenly, and obtain a mixed solution;

[0065] S2, adding 3 ml of 1 mol / L sodium hydroxide solution and 0.52 g of ammonium hypophosphite to the mixed solution obtained in step S1, stirring for 0.5 h, and then placing the mixture in a reactor and heating at 100° C. for 8 h to obtain a reaction solution;

[0066] S3, cooling the reaction solution obtained in step S2 to room temperature and washing with distilled water until the supernatant is neutral, washing with anhydrous ethanol for the last time, and vacuum drying the product at 60° C. for 12 h to obtain a titanium dioxide-silver composite material modified with phosphate groups.

[0067] The modified nano titanium dioxide is prepared by the following method:

[0068] S101, ultrasonically dispersing 1 g of nano-titanium dioxide into 17.5 g of a mixed solution containing deionized water, ethanol and ethyl propionate, wherein the masses of deionized water, ethanol and ethyl propionate are 12.5 g, 3.75 g and 1.25 g, respectively, and the frequency of the ultrasonic wave is 19 kHz, and then sodium hydroxide is added to adjust the pH of the solution to 9;

[0069] S102, adding 1.6 g of carboxymethyl chitosan, 0.175 g of tetraethylene glycol monooctyl ether and 0.31 g of sodium styrene sulfonate to the mixed solution of deionized water, ethanol and ethyl propionate in step S101, mixing and placing in a reactor to react at 100° C. for 5 h;

[0070] S103, filtering the reaction liquid in the reaction kettle after the reaction in step S102, washing with ethanol, and vacuum drying at 240° C. to obtain modified nano titanium dioxide.

[0071] The nano titanium dioxide in the above embodiments is prepared by the following method:

[0072] 6 mL of tetrabutyl titanate was added to 150 mL of ethylene glycol, and then heated to 120°C and refluxed for 1 hour after ultrasonic treatment for 10 minutes. After the reaction was completed, 60 mL of water was added to the precursor obtained after centrifugation, and then calcined at 500°C for 2 hours to obtain nano titanium dioxide.

[0073] The XRD analysis of the final product obtained in Example 1 proved that the synthesized TiO2 Anatase TiO 2 Its diffraction peak is consistent with the standard spectrum 21-1272Anatase, and no other impurity peaks appear, indicating that TiO 2 The successful synthesis of PO 4 3- -TiO 2 -Ag composite materials correspond to the diffraction peaks of TiO 2 (21-1272) and Ag(1-1164), among which the diffraction peaks of Ag are near 44° and 64° in the composite material, indicating the successful construction of the composite material.

[0074] In order to further prove the composite material composition and element valence of the synthetic material, XPS analysis was performed on the composite material synthesized in Example 1, proving that the composite material synthesized in this example is composed of five elements: Ti, Ag, O, P and C, where C is the carbon element introduced in the test. The results further confirmed the element composition of the composite material. Through single element valence analysis, the Ti element exists in the form of +4 valence; the difference between the spin-orbit splitting peaks of the Ag element is 6.0 eV, proving that the main existence form of the Ag element is single substance Ag; the XPS results further confirmed that PO 4 3- -TiO 2 -Synthesis of Ag composites.

[0075] Figure 3 and Figure 4 They are respectively the modified nano-TiO 2 and PO 4 3- -TiO 2 -Ag composite material SEM image, it can be seen that TiO 2 The surface has a porous structure, and the morphology does not change after solvent thermal treatment. The particle size of Ag nanoparticles is extremely small. 2 The surface distribution is uniform without aggregation, and the product has good catalytic effect.

[0076] Figure 5 PO obtained in this example 4 3- -TiO 2 -Ag composite material TEM image, TiO 2 (101) and Ag(111) exist, and the particle size of Ag is about 10-20nm.

[0077] The PO obtained in this example 4 3- -TiO 2 -Ag composite materials, TiO2 and the control group without silver salt 4 3- -TiO 2 Photocatalytic reduction of CO 2 Activity test, the specific steps include: 1mL deionized water is dripped into 50mg catalytic sample (PO 4 3- -TiO 2 -Ag composite materials, monomer TiO 2 Or the control group without silver salt PO 4 3- -TiO 2 ), and after ultrasonication for 2 minutes, the samples were evenly placed in a culture dish with a diameter of 3.4 cm. 10 mL of deionized water was added to the bottom of the photoreactor, and then the culture dish was placed in the bottom of the reactor. High-purity CO was passed through the reactor for 30 minutes. 2 The air in the reactor was removed by gas, and then the photoreactor was closed and irradiated with a 300W Xe lamp. 1 mL of the gaseous product was taken every hour and the components were analyzed by gas chromatography until the irradiation was completed after 4 hours.

[0078] The results are as follows Figure 6 As shown, the test results show that PO 4 3- -TiO 2 The photocatalytic activity is better than that of TiO 2 , P.O. 4 3- -TiO 2 -Ag composites are significantly more active than TiO 2 and PO 4 3- -TiO 2 .

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a porous titanium dioxide-silver composite material modified with a phosphate group, characterized in that: The steps include: S1. Ultrasonic dispersion of modified nano-titanium dioxide into deionized water, adding 1 mol / L silver nitrate solution, stirring evenly to obtain a mixed solution; S2, adding 1 mol / L sodium hydroxide solution and ammonium hypophosphite to the mixed solution obtained in step S1, stirring for 0.4-0.8 h, putting it into a reactor and heating it at 40-140° C. for 6-24 h to obtain a reaction solution; S3, cooling the reaction solution obtained in step S2 to room temperature and washing with distilled water until the supernatant is neutral, washing with anhydrous ethanol for the last time, and vacuum drying the product at 50-80° C. for 10-16 h to obtain a titanium dioxide-silver composite material modified with a phosphate group; The modified nano titanium dioxide in step S1 is prepared by the following method: S101, ultrasonically dispersing nano-titanium dioxide into a mixed solution of deionized water, ethanol and ethyl propionate, and then adding sodium hydroxide to adjust the pH of the solution to 8-11; S102, adding carboxymethyl chitosan, tetraethylene glycol monooctyl ether and sodium styrene sulfonate to the mixed solution of deionized water, ethanol and ethyl propionate in step S101, and then putting the mixture into a reactor to react at 80-160° C. for 4-10 hours; S103, filtering the reaction liquid in the reaction kettle after the reaction in step S102, washing with ethanol, and vacuum drying at 150-250° C. to obtain modified nano titanium dioxide; In the step S101, the mass ratio of ethyl propionate, ethanol and deionized water is 1:3:10, and the mass ratio of nano-titanium dioxide to the mixed solution of deionized water, ethanol and ethyl propionate is 1:(10-30); In the step S102, the mass ratio of the mixed solution of tetraethylene glycol monooctyl ether, sodium styrene sulfonate and carboxymethyl chitosan to deionized water, ethanol and ethyl propionate is 1:(1-3):(5-10):(80-120).

2. The method for preparing the porous titanium dioxide-silver composite material modified with phosphate groups according to claim 1, characterized in that: In the step S1, the mass ratio of the modified nano titanium dioxide to the deionized water is 1:(100-250), and the volume ratio of the silver nitrate solution to the deionized water is 1:(260-580).

3. The method for preparing the porous titanium dioxide-silver composite material modified with phosphate groups according to claim 1, characterized in that: The volume ratio of the sodium hydroxide solution in step S2 to the deionized water in step S1 is 1:(15-28), and the mass ratio of the ammonium hypophosphite in step S2 to the modified nano titanium dioxide in step S1 is 1:(0.73-1.73).

4. A titanium dioxide-silver composite material modified with a phosphate group, characterized in that: The composite material is prepared by the method for preparing a porous titanium dioxide-silver composite material modified with phosphate groups as described in any one of claims 1 to 3.

5. Use of the titanium dioxide-silver composite material modified with phosphate groups prepared by the preparation method according to any one of claims 1 to 3 or the titanium dioxide-silver composite material modified with phosphate groups according to claim 4 in the field of preparing hydrocarbon fuels by photocatalytic carbon dioxide reduction.

6. The use of the phosphoric acid group-modified titanium dioxide-silver composite material according to claim 5 in the field of photocatalytic carbon dioxide reduction to prepare hydrocarbon fuels, characterized in that: Use the following method: The titanium dioxide-silver composite material modified with phosphate groups is uniformly mixed with deionized water, and catalytically converts carbon dioxide under light.

Citation Information

Patent Citations

  • Titanium dioxide-based catalyst preparation method (options)

    RU2243033C1